Internal flow pattern of the condenser section that affects the heat transfer characteristics of rectangular two-phase closed thermosyphon - Kittipon Khaongam; Teerapat Chompookham; Thanya Parametthanuwat (Case Studies in Thermal Engineering)
This research examines the internal flow patterns within the condenser and evaporator sections that influence the heat transfer characteristics of a rectangular two-phase closed thermosyphon (RTPCT). The thermosyphon has wetted perimeters of 25.2 mm on both the X and Y sides and aspect ratios (AR) of 5, 10, and 20. The study considers inclination angles of 70°, 80°, and 90°, with evaporator temperatures set at 50 °C, 70 °C, and 90 °C. The cooling water temperature is fixed at 20 °C. The working fluids include deionized water (DI), deionized water with 0.5 wt% silver nanoparticles (NP), oleic acid at 1 wt% (OA), NP with 1 wt% potassium oleate (OAK+), and ethanol. The filling ratio in the evaporator section is maintained at 50 %. Experimental results indicate that at an evaporator temperature of 50 °C, no flow occurs in either section. At evaporator temperatures of 70 °C and 90 °C, the flow patterns in the condenser section for ARs of 5, 10, and 20, using DI and ethanol, exhibit film-wise and rivulet flows. For DI with 0.5 wt% silver nanoparticles (NP), 1 wt% oleic acid (OA), and NP with 1 wt% potassium oleate (OAK+), the flow patterns observed include fluctuation flow, dropwise flow, and rivulet flow. In the evaporator section, the flow patterns for DI with AR 5 include bubble flow, slug flow, and churn flow. For ARs 10 and 20, the patterns observed are bubble flow, slug flow, churn flow, and annular flow. At an evaporator temperature of 90 °C, stratified flow is observed at inclination angles of 70° and 80°. Working fluids such as ethanol and DI with 0.5 wt% silver nanoparticles (NP), 1 wt% oleic acid (OA), and NP with 1 wt% potassium oleate (OAK+), across ARs 5, 10, and 20, demonstrate bubble flow and churn flow. These conditions provide higher liquid- and vapor-phase momentum fluxes than DI and ethanol alone. An inclination angle of 80° yields a higher heat transfer rate compared to 70° and 90°, achieving a maximum heat flux of 8.16 kW/m2